New quaternary Corynanthé alkaloid from Lerchea bracteata - Arbain, Dayar; Lajis, Nordin H.; Putra, Deddi Prima; Sargent, Melvyn V.; Skelton, Brian W.; White, Allan H. (Royal Society of Chemistry (RSC), 1992)
Extraction of the leaves of Lerchea bracteata Val. (Rubiaceae) has yielded a quaternary Corynanthé alkaloid, dihydro-3-epi-corynantheol methochloride (lercheine) 4 the structure of which followed from analysis of its spectral data and by X-ray crystal structure determination of the corresponding bromide.